2018
DOI: 10.1021/acsaem.8b00007
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Performance of Germanium Halide Perovskite Solar Cells through Compositional Engineering

Abstract: Germanium halide perovskites are an attractive alternative to lead perovskites because of their well-suited optical properties for photovoltaic applications. However, the power conversion efficiencies of solar cells based on germanium perovskites remained below 0.2% so far, and also, the device stability is an issue. Herein, we show that modifying the chemical composition of the germanium perovskite, i.e., introducing bromide ions into the methylammonium germanium iodide perovskite, leads to a significant impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
172
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(180 citation statements)
references
References 17 publications
1
172
0
Order By: Relevance
“…The CBM is derived from antibonding states of Ge 4p and I 5p orbitals. [78] So far, there have been only a few reports on Ge halide perovskite solar cells, [75,82] which is likely due to the instability of the Ge 2+ toward oxidation to Ge 4+ . Because of the p-p transition, CsGeI 3 exhibits high optical absorption coefficients, comparable to those for Pb halide perovskites.…”
Section: Wwwadvmatde Wwwadvancedsciencenewscommentioning
confidence: 99%
See 1 more Smart Citation
“…The CBM is derived from antibonding states of Ge 4p and I 5p orbitals. [78] So far, there have been only a few reports on Ge halide perovskite solar cells, [75,82] which is likely due to the instability of the Ge 2+ toward oxidation to Ge 4+ . Because of the p-p transition, CsGeI 3 exhibits high optical absorption coefficients, comparable to those for Pb halide perovskites.…”
Section: Wwwadvmatde Wwwadvancedsciencenewscommentioning
confidence: 99%
“…However, theoretical calculations by Ming et al indicated that the Ge vacancy in CsGeI 3 is the dominant defect with shallow transition levels and rather low formation enthalpy, which yields a very high-density of holes, particularly at Ge-poor synthesis conditions. Recently, Kopacic et al [82] demonstrated that chemical composition engineering of MAGeI 3 by introducing bromide anions leads to a significant improvement in solar cell performance along with a slight enhancement of the material stability. [78] So far, there have been only a few reports on Ge halide perovskite solar cells, [75,82] which is likely due to the instability of the Ge 2+ toward oxidation to Ge 4+ .…”
Section: Wwwadvmatde Wwwadvancedsciencenewscommentioning
confidence: 99%
“…By substituting 10% I − with Br − a PCE of 0.57% was achieved (Table 1) in an inverted cell with a fullerene ETL [144]. …”
Section: Reviewmentioning
confidence: 99%
“…Generally, the A site is occupied by a monovalent organic or inorganic cation (e.g., CH 3 NH 3 + (MA); HC(HN 2 ) 2 + (FA); Cs + ; Rb + ), the B is often a metal cation (e.g., Pb 2+ ; Sn 2+ ), and the X is typically a halide anion (e.g., Cl‐; Br – ; I – ; SCN – ). Compositional engineering of the hybrid metal halide perovskite or inorganic perovskite materials with mixed cations and halides is an effective strategy to achieve further improvements in PCE and long‐term stability of the devices …”
Section: Introductionmentioning
confidence: 99%